Responsibilities of Notaries Receiving Protocols from Notaries Who Die in Kendal Regency - Rijal, Al (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Notary Protocol is a collection of documents that are State archives that must be stored and maintained by a Notary in accordance with the provisions of laws and regulations. As an important document belonging to the State that functions as evidence, the Notary Protocol should be properly maintained. The storage of the Notary Protocol by the Notary holding the protocol is an effort to maintain the legal age of the Notary deed as perfect evidence for the parties or their heirs regarding everything contained in the deed.t. The position of the Protocol Recipient only includes those who have resigned, retired or died. Based on the results of this study, the responsibility of the Notary who receives the protocol from a Notary who has died in Kendal Regency. The Notary who receives the protocol in Kendal Regency is only responsible for storing and maintaining the Protocol he receives and for providing information related to the protocol in his possession, because this is one of the responsibilities of the recipient of the notary protocol, however, the notary who receives the protocol will still be called to ask for information if there is a problem.Keywords: Protocol; Responsibility; Notary.